Role of socio-demographic and cultural factors on anemia in a tribal population of North Kerala, India - Ismail, Imaad Mohammed; Kahkashan, Azeez; Antony, Alwin; VK, Sobhith (International Journal Of Community Medicine And Public Health, 2017)
Background: Anemia is a major public health problem in India, with an estimated prevalence of 38% to 82% in non-pregnant females and 18% to 59% in males. Anemia is a major cause for maternal mortality and chronic anemia leads to secondary organ damage such as congestive heart failure. Tribal people have been observed to have a higher prevalence of anemia and the factors causing it varies according to their geographical location and cultural practices; hence this study was undertaken with the objective of estimating the prevalence of anemia and identifying its risk factors among residents of Kannavam tribal area, Kerala, India. Methods:It was a cross-sectional study conducted among tribal residents of Kannavam area from May 2014 to October 2015. Using convenient sampling 200 tribal people aged 18 years and above were selected, interviewed and sample collected. Anaemia was classified according to WHO criteria. Proportions, chi-square test and regression were used for analysis and p value less than 0.05 was considered to be significant. Results: The mean (±SD) age of the study participants was 43 (±16) years. 43.5% study participants were males and the rest were females. The overall prevalence of anemia in the currently study is 51% (33.3% in males and 64.6% in females) which is much higher than the Kerala state prevalence rates. Increasing age and low socio-economic class were found to be common risk factors associated with anemia among both sexes whereas menorrhagia was found to be a significant factor in females. Conclusions:The prevalence of anemia was high among both male and female tribal residents. Geriatric age group and low socio-economic status people were particularly vulnerable for developing anemia and special focus must be given to them while administering preventive and control measures.